The World Bank's Country Policy and Institutional Assessment : An IEG Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2013)
The World Bank's Country Policy and Institutional Assessment (CPIA) assess the conduciveness of a country's policy and institutional framework to poverty reduction, sustainable growth, and the effective use of development assistance. The CPIA enters the calculation of country performance ratings that, since 1980, have been used to allocate International Development Association (IDA) resources to eligible client countries. This evaluation was undertaken at the request of Board members to assess the appropriateness of the CPIA as a broad indicator of development effectiveness and as a determinant of the allocation of IDA funds. As indicated in the approach paper, this evaluation reviews the effects of the CPIA ratings on IDA allocations but does not review the IDA allocation formula itself. The evaluation finds that the CPIA content broadly reflects the determinants of economic growth and poverty reduction identified in the economics literature, but some criteria need to be revised (such as the trade criterion that places much greater emphasis on imports than exports) and streamlined, and one criterion (assessment of disadvantaged socioeconomic categories other than gender) added. The CPIA ratings also correlate well with ratings of similar indicators, and more so for International Bank for Reconstruction and Development than for IDA countries. In part, this could be caused by the CPIA exercise's practice over the past several years of taking into account a country's stage of development, which also means that the CPIA is no longer an index in the true sense of the word. It is difficult to establish an empirical link between the CPIA and economic growth outcomes, although CPIA ratings are found to be positively associated with aid effectiveness in the narrower sense-specifically, the performance of Bank loans. The report lays out four recommendations: disclose International Bank for Reconstruction and Development ratings; discontinue the "stage of development" adjustment to the ratings; review and revise the content and clustering of the criteria; and discontinue the current aggregation of the criteria into an overall index.